Актопротекторна активність солей (3-R-оксо-2Н-[1,2,4]-тріазино [2,3-с] хіназолін-6-іл) карбонових кислот та їхніх галогенвмісних аналогів - Степанюк, Г. І.; Почелова, О. В.; Степанюк, Н. Г.; Коваленко, Сергій Іванович; Воскобойнік, Олексій Юрійович; Stepanyuk, G. I.; Pochelova, E. V.; Stepanyuk, N. G.; Kovalenko, S. I.; Voskoboynik, A. Y. (My University, 2014)
Актопротектори – це засоби, що запобігають виникненню втоми та покращують працездатність за звичайних та екстремальних умов (гіпоксія, гіподинамія, високі та низькі температури тощо). Нині вказаний клас фармпрепаратів представлений практично одним бемітилом. Слід також враховувати недостатню ефективність останнього та наявність у нього побічних ефектів, які обмежують використання препарату в клініці [6]. До того ж бемітил в Україні не випускають, хоча потреба в таких засобах, без сумніву, велика. The purpose of the study was to evaluate the actoprotective effects of salts of (3-R-oxo-2Н-[1,2,4]- triazino[2,3-с] quinazolin-6-yl) carboxylic acids and their halogen containing analogues, to identify compounds – leaders, suitable for in-depth study of their pharmacological properties. The actoprotective activities of the compounds were evaluated on white rats by the duration of swimming test in water (24–26 °C) with the additional load (10 % of body weight). There were established that single intraperitoneal administration to animals (3-R-oxo-2Н-[1,2,4]- triazino[2,3-с] quinazolin-6-yl) carboxylic acids derivatives in the empiric taken dose 10 mg/kg, as well as bemityl (50 mg/kg), caused an increase of the duration of swimming test. Marked increase of the physical endurance of rats induced by the test compounds provided the evidence of their actoprotective activity. The greatest abilities to promote physical endurance of animals showed the compounds under laboratory code AV-224, DSK-38, AV-227 and DSK-39: under their action the duration of swimming test elongated accordingly by 318, 291, 205 and 171 % against 141 % under influence of bemityl as to control group. It was established that actoprotective effects of these compounds as bemityl are dose dependent. Leader compounds were superior comparator drug bemityl about 6,1–8,1 times on the value of ED50. The highest activities were characterized for the compounds that contain carboxyalkyl (carboxypropyl or carboxybutyl) substituents at position 6 and methyl radicals with aryl substituents (methoxy, flyuoro-, isopropyl) at position 3 which led to an increase the lipophilicity of the molecule. The results obtained indicate the prospects of in-depth study the pharmacological properties of the leader compounds to create a new actoprotector.
An actoprotective activity of salts of (3-R-oxo-2Н-[1,2,4]-triazino[2,3-с] quinazolin- 6-yl) carboxylic acids and their halogen containing analogues
Keywords: актопротекторна активність; похідні (3-R-оксо-2Н-[1,2,4]- тріазино-[2,3-с]-хіназолін-6-іл) карбонових кислот; бемітил; плавальний тест; actoprotective activity; derivatives of (3-R-oxo-2H-[1,2,4] triazino [2,3-c] quinazolin-6-yl) carboxylic acid; bemityl; swimming test